1999
DOI: 10.1074/jbc.274.12.8282
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Kilobase Pair Promoter Fragment of the Murine Epididymal Retinoic Acid-binding Protein Gene Drives the Tissue-specific, Cell-specific, and Androgen-regulated Expression of a Foreign Gene in the Epididymis of Transgenic Mice

Abstract: The murine epididymis synthesizes and secretes a retinoic acid-binding protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…This result independently confirms the previous report from the laboratory of Orgebin-Christ, in which a CAT reporter gene under the 5-kb promoter 8 control is specifically expressed in the mouse caput epididymidis. The mE-RABP gene promoter effectively overexpressed mBin1b at levels of up to 50-fold higher than WT mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result independently confirms the previous report from the laboratory of Orgebin-Christ, in which a CAT reporter gene under the 5-kb promoter 8 control is specifically expressed in the mouse caput epididymidis. The mE-RABP gene promoter effectively overexpressed mBin1b at levels of up to 50-fold higher than WT mice.…”
Section: Discussionsupporting
confidence: 92%
“…Gene expression was driven by the previously reported epididymis-specific promoter of the mE-RABP gene. 8 The mBin1b TG construction was shown in Figure 3a. The mBin1b TG founder mice were identified via PCR detection of the mouse tail genomic DNA (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…One could hypothesize that the clustered organization of the mEP17(Lcn8), mE-RABP(Lcn5), mLcn9 and mLcn10 genes may be required for tissue and region-specific expression. Indeed, it has been shown that 5 kb of the 5Vflanking region of the mE-RABP(Lcn5) gene and 5.3 kb of the 5V flanking region of the mEP17(Lcn8) gene contain all the information to target foreign gene expression to either the distal caput epididymidis (Lcn5) or the initial segment (Lcn8) in transgenic mice (Lareyre et al, 1999;Suzuki et al, 2003). Further studies will be required to identify DNA regions involved in the regionalization of the expression of the epididymal lipocalin gene cluster.…”
Section: Lipocalins Encoded By the Epididymal Lipocalin Gene Cluster mentioning
confidence: 99%
“…The epididymis of this transgenic mouse strain synthesizes a CAT reporter gene upstream of a retinoic acid-binding protein promoter (mE-RABP). The gene is specifically expressed in mouse mid/distal caput epididymis under the control of androgen (Lareyre et al 1999(Lareyre et al , 2000. Seven females were dosed with 0.1 mL/day corn oil, and seven females were dosed with 10 mg/kg/day HCB in corn oil.…”
Section: Methodsmentioning
confidence: 99%
“…Our novel and highly sensitive in vivo approach used two strains of transgenic mice to test the impact of HCB on hormone action. The mE-RABP-CAT and LPB-CAT mouse express the chloramphenicol acetyl transferase (CAT) reporter gene under the direction of a highly androgen-sensitive promoter in the epididymis and prostate, respectively (Lareyre et al 1999(Lareyre et al , 2000Yan et al 1997). HCB decreased CAT expression and prostate weights in both strains of mice.…”
Section: Disruption Of Androgen Regulation In the Prostate By The Envmentioning
confidence: 99%